Evaluation of Thyroid Function in Patients Hospitalized for Acute Heart Failure - Ana Rita Leite; João Sérgio Neves; Marta Borges-Canha; Catarina Vale; Madalena von Hafe; Davide Carvalho; Adelino Leite-Moreira (International Journal of Endocrinology)
Background. Thyroid hormones (TH) are crucial for cardiovascular homeostasis. Recent evidence suggests that acute cardiovascular conditions, particularly acute heart failure (AHF), significantly impair the thyroid axis. Our aim was to evaluate the association of thyroid function with cardiovascular parameters and short- and long-term clinical outcomes in AHF patients. Methods. We performed a single-centre retrospective cohort study including patients hospitalized for AHF between January 2012 and December 2017. We used linear, logistic, and Cox proportional hazard regression models to analyse the association of thyroid-stimulating hormone (TSH) and free thyroxine (FT4) with inpatient cardiovascular parameters, in-hospital mortality, short-term adverse clinical outcomes, and long-term mortality. Two models were used: (1) unadjusted, and (2) adjusted for age and sex. Results. Of the 235 patients included, 59% were female, and the mean age was 77.5 (SD 10.4) years. In the adjusted model, diastolic blood pressure was positively associated with TSH [β = 2.68 (0.27 to 5.09); p=0.030]; left ventricle ejection fraction (LVEF) was negatively associated with FT4 [β = -24.85 (-47.87 to -1.82); p=0.035]; and a nonsignificant trend for a positive association was found between 30-day all-cause mortality and FT4 [OR = 3.40 (0.90 to 12.83); p=0.071]. Among euthyroid participants, higher FT4 levels were significantly associated with a higher odds of 30-day all-cause death [OR = 4.40 (1.06 to 18.16); p=0.041]. Neither TSH nor FT4 levels were relevant predictors of long-term mortality in the adjusted model. Conclusions. Thyroid function in AHF patients is associated with blood pressure and LVEF during hospitalization. FT4 might be useful as a biomarker of short-term adverse outcomes in these patients.